Dinamika Kuasa Adat, Kekerabatan, dan Kemunduran Budaya: Studi Kritis atas Transformasi Sosial di Nagari Peninggalan Kerajaan Pagaruyung - Ramadhan, Al Hafiz Rasya; Yusuf, Hudaidah (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
The Kingdom of Pagaruyung was one of the most important centers of culture and government in Sumatra in the past, especially for the Minangkabau people. This article discusses descriptively the role of the Pagaruyung Kingdom in shaping the social structure, government system, and the development of customary and religious values in the Minangkabau environment. Using a qualitative approach through a literature study, this article explores how the Rajo Tigo Selo collective government system was implemented, as well as how customary law and matrilineal structure played a role in maintaining social harmony. In addition, the integration of adat and Islam is the main force that makes Pagaruyung a center of cultural value stability that has been preserved to this day. Despite the kingdom's political decline due to colonialism and internal conflict, its influence remains strong in the lives of Minang people today, making it a living symbol of cultural heritage. This article aims to strengthen the understanding of Pagaruyung's importance in Minangkabau history and identity as a whole. Kerajaan Pagaruyung merupakan salah satu pusat kebudayaan dan pemerintahan terpenting di wilayah Sumatra pada masa lampau, khususnya bagi masyarakat Minangkabau. Artikel ini membahas secara deskriptif tentang peran Kerajaan Pagaruyung dalam membentuk struktur sosial, sistem pemerintahan, serta pengembangan nilai-nilai adat dan keagamaan di lingkungan Minangkabau. Dengan menggunakan pendekatan kualitatif melalui studi literatur, artikel ini menelusuri bagaimana sistem pemerintahan kolektif Rajo Tigo Selo dijalankan, serta bagaimana hukum adat dan struktur matrilineal berperan dalam menjaga harmoni sosial. Selain itu, integrasi antara adat dan Islam menjadi kekuatan utama yang menjadikan Pagaruyung sebagai pusat stabilitas nilai budaya yang lestari hingga kini. Meskipun secara politik kerajaan ini mengalami kemunduran akibat kolonialisme dan konflik internal, pengaruhnya tetap kuat dalam kehidupan masyarakat Minang masa kini, menjadikannya simbol warisan budaya yang hidup. Artikel ini bertujuan untuk memperkuat pemahaman akan pentingnya Pagaruyung dalam sejarah dan identitas Minangkabau secara menyeluruh.